2022
DOI: 10.1108/ejim-05-2022-0238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knowledge resources on innovation and the mediating role of dynamic capabilities: case of medical tourism sector in Iran

Abstract: PurposeThis research is an empirical study that addresses whether knowledge resources impact on, or do not impact on, innovation development and if this impact is mediated by dynamic capabilities in the medical tourism sector in Mashhad city, Iran.Design/methodology/approachA quantitative research methodology was applied and questionnaires were used for data collection in this study. A total of 108 questionnaires were collected of which 102 questionnaires were valid. Data were analyzed using structural equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 129 publications
0
4
1
Order By: Relevance
“…This evidence contradicts with some earlier findings (Huang & Li, 2017;Qiu et al, 2020;Singh et al, 2019;Yousaf, 2021). Edgar et al (2024) found that DC of learning is influential in transforming knowledge resources into innovation for Iranian firms. However, Wilden et al (2013) and Zhou et al (2019) discuss DC have different effects.…”
Section: Empirical Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…This evidence contradicts with some earlier findings (Huang & Li, 2017;Qiu et al, 2020;Singh et al, 2019;Yousaf, 2021). Edgar et al (2024) found that DC of learning is influential in transforming knowledge resources into innovation for Iranian firms. However, Wilden et al (2013) and Zhou et al (2019) discuss DC have different effects.…”
Section: Empirical Findingscontrasting
confidence: 99%
“…Ar, 2012;Barforoush et al, 2021;Dangelico et al, 2017;Gürlek & Tuna, 2018;Jabarzadeh et al, 2022;Şengüllendi et al, 2023;Yousaf, 2021;Yurdakul & Kazan, 2023) and partial least squares-structural equation modelling (e.g. Aboelmaged & Hashem, 2019;Albort-Morant et al, 2016 ;Ahmad et al, 2024;Awan et al, 2021;Bhatia & Jakhar, 2021;Edgar et al, 2024) are the most frequently-used techniques in the GI adoption or performance literature. Apart from those techniques, many earlier studies have also utilized from regression analysis (Jahanshahi et al, 2020;Leenders & Chandra, 2013;Qiu et al, 2020;Sezen & Yıldız Çankaya, 2013;Tepe Küçükoğlu & Pınar, 2015;Zhang & Zhu, 2019), partial least squares-path modelling approach (Albort Morant et al, 2018b;Singh et al, 2022), multi-criteria decision-making (Fahad et al, 2022;Musaad et al, 2020), hierarchical linear modelling (Xue et al, 2019;Zhang et al, 2020), confirmatory factor analysis (Lin & Chen, 2017) to analyze GI adoption or performance.…”
Section: Introductionmentioning
confidence: 99%
“…Because tourism was among the business sectors most negatively affected by the COVID-19 pandemic (Senbeto and Hon, 2020), TSMEs were chosen for this investigation. Also, most DC studies dealt with the production sector, with few focused on service companies such as those in tourism (Edgar et al , 2022). Wided (2022) argued that DCs were vital for achieving sustainable tourism.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, industrial integration has become a new driving force for promoting the evolution of tourism industry models and formats (Lu, 2011). Research on the integration of the tourism industry has gradually refined and matured, and the content has become more and more extensive, such as the integration of tourism and the cultural industry (Bordoni, 2011), sports industry (Zhu, 2022) and medical industry (Edgar et al, 2022;Parekh et al, 2021). Due to the different integration parties, the integration development models also vary.…”
Section: Literature Reviewmentioning
confidence: 99%